THE FORMATION OF TRUST: A STUDY IN THE UNIBRASPE'S POOL - Pirani, Sérgio Luiz; Cunha, Cleverson Renan da (Revista de Administração da UFSM, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The theme of this work is the formation of Trust in the UNIBRASPE's pool. The objective of this assignment was to identify the structure and evolution of interorganisational relationships. The evolution of trust was detected through observation, semi-structured interviews and questionaires characterizing this survey as a descriptive-analitical case study. We can conclude that the structure of the network is a condition for good relationships between its members, permitting formal and informal norms complement to the pool's gestation. It was also noted that the evolution of trust came about through the previous knowledge of the people studied which made it possible for their to be a closer relationship between the organizations.